2013
DOI: 10.3390/nu5041110
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dietary Supplements in Patients Seeking Treatment at a Periodontal Clinic

Abstract: Dietary supplement use may modify the risk of periodontal disease but effects on wound healing after periodontal procedures are less clear. This study characterized dietary supplement use by male and female patients (n = 376) attending a periodontal clinic—information that is essential for evidence-based intervention studies that may improve patient outcomes after periodontal procedures. Calcium, vitamin D, multivitamin and vitamin C were most commonly used. A greater (p ≤ 0.05) number of males took no supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Moreover, the findings are largely generalizable to the overall adult population as both sexes and a range of adult ages were included. This study also shows that supplement use had remained fairly consistent over time when compared to a similar study previously conducted among this population (Johnston et al, 2013). It was previously reported that 64.1% of patients attending this clinic for general examination or surgical consultation were taking dietary supplements (Johnston et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, the findings are largely generalizable to the overall adult population as both sexes and a range of adult ages were included. This study also shows that supplement use had remained fairly consistent over time when compared to a similar study previously conducted among this population (Johnston et al, 2013). It was previously reported that 64.1% of patients attending this clinic for general examination or surgical consultation were taking dietary supplements (Johnston et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…This study also shows that supplement use had remained fairly consistent over time when compared to a similar study previously conducted among this population (Johnston et al, 2013). It was previously reported that 64.1% of patients attending this clinic for general examination or surgical consultation were taking dietary supplements (Johnston et al, 2013). The patients included in this present study—patients undergoing implant or soft tissue graft surgery—are of particular interest because following their surgery, they could be in a position to further support their recovery by adding dietary supplements to their post‐surgical care (Gorecki et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There is a growing body of evidence to indicate that selected macro and micronutrients, in sufficient levels, are not only essential for the development of tooth structures but may also play a role in modifying the progression and treatment outcomes of periodontal disease [8,31]. Further, the increasing use of dietary supplements by the general public and the possibility of interactions with prescription medication make it imperative that oral health providers be erudite about the role of nutrition in the general and oral health of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is considered to be the main cause of tooth loss in adults [6]. Recently though, an increasing body of evidence from dietary intervention studies has investigated the effect of several macro and micronutrients on the health of the periodontium and on attenuating the disease process [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%